Differences in the presentation and outcome between premenopausal and postmenopausal primary hyperparathyroidism Indian women: A single-center experience - Aasim N Maldar; Nishitkumar F Shah; Phulrenu H Chauhan; Murad Lala; Milind V Kirtane; Manoj Chadha (Wolters Kluwer Medknow Publications, 2023)
Introduction: Primary hyperparathyroidism (PHPT) is an endocrine disorder wherein enlargement of one or more of the parathyroid glands causes autonomous overproduction of the parathyroid hormone (PTH), which leads to high serum calcium levels. Objective: The objective of this study was to compare the clinical, laboratory, and operative variables between premenopausal (pre-M) and postmenopausal (post-M) women with PHPT. Materials and Methods: A retrospective analysis of the data of female patients who underwent surgery for PHPT at a single center, from January 2011 to December 2020, was done. Patients with familial PHPT and secondary hyperparathyroidism were not included. Results: Of the 130 women with PHPT, 44.6% were pre-M and 55.4% were post-M. A significantly higher number of pre-M females were symptomatic compared to post-M females (pre-M vs. post-M, 84.5% vs. 68.1%, P = 0.031). Renal calculi were more common in pre-M women (34.5% vs. 18.1%, P = 0.032), while the rest of the clinical features were comparable between the two groups. The proportion of women with osteoporosis (6.7% vs. 19.4%, P = 0.071), hypertension (13.8% vs. 34.7%, P = 0.012), and diabetes mellitus (3.5% vs. 16.7%, P = 0.033) was lesser in the pre-M group. Elevated serum alkaline phosphatase levels were significantly more prevalent in the pre-M group (37.9% vs. 20.8%, P = 0.032). The mean serum calcium (12.35 ± 1.28 vs. 11.96 ± 1.22 mg/dL, P = 0.079), median serum PTH (334 vs. 239 pg/mL, P = 0.051), and median weight of the operated adenomas (1.75 vs. 1.45 g, P = 0.075) were also higher in pre-M females. The proportion of ectopic adenomas and multiple adenomas, presurgery adenoma localization rates, and disease cure rates did not differ according to the menopausal status. The occurrence of postoperative hungry bone syndrome was higher in the pre-M women (15.5% vs. 1.4%, P = 0.008). Conclusion: The majority of women with PHPT are post-M, but symptomatic presentation is more common in pre-M females. The severity of the disease appears to be more in pre-M women; however, imaging and operative variables generally did not significantly differ between the two groups.